Future-Ready Finance: Adapting to the New Financial Landscape - Neltje Meini Rotinsulu, Clara; Saeful Falah , Asep; Tresnasari , Rini; Sarbaeni, Sarbaeni (International Journal of Economics Development Research (IJEDR), 2024)
This study examines the influence of financial regulatory policies and technological innovation on future financial readiness, with a particular focus on the mediating role of business strategy adaptation. Using a quantitative research design, data were collected from 267 Bank Syariah Indonesia (BSI) mobile banking users, primarily university students. The analysis, conducted via Smart PLS, reveals that both regulatory policies and technological advancements significantly impact future financial readiness when mediated by an adaptive business strategy. While regulatory compliance and technological adoption are essential, they do not directly enhance financial preparedness without strategic adaptation, which allows organizations to respond proactively to changing market conditions. Notably, for Islamic banking institutions like BSI, aligning dual compliance with adaptive strategies is critical for balancing Sharia and regulatory requirements with innovative capabilities. This study underscores the importance of a flexible, adaptive approach in achieving financial resilience, positioning adaptive business strategies as a key driver of sustainable competitive advantage within the evolving financial landscape.